DIGITISED IDENTITY OF MALAY LANGUAGE LEARNERS AT THE TERTIARY LEVEL: IDENTITI DIGITAL PELAJAR BAHASA MELAYU PADA PERINGKAT PENGAJIAN TINGGI - Sew, Jyh Wee (Jurnal Pengajian Melayu (JOMAS), 2020)
AbstractThe digitised format is the current norm in the pedagogy of foreign language. There is much interest in the symbolic transactions underlining the development of semiotic identity in blog-based foreign language literacy. This discussion assumed that blogging is an expression of oneself online, thus the content of the blog posts is construable as the make-up of a digitised identity of the learner. Based on a review of existing studies that examined identity development in the form of a textual self, this discussion introduced the notion of digitised identity that arose from computer-mediated communication. The approach to trace digitised identity involved scrutiny of blog posts assigned to the foreign language learners for journaling Malay language learning at the tertiary level. Observing the digitised styling as shown by Malay language learners’ managing of online content in their blogs offers some interesting pointers towards an understanding of a digitised identity of the immaterial self. Based on the design and presentation of the blog entries among selected Malay language learners, this study observed a change from ritualistic blogging to an online language display. The use of multiple semiotic assortments, which are reflective of the foreign language learners’ stance, is indicative of a digitised expression of self. The observation identified a potential area of e-learning awaiting exploits in the pedagogy of Malay as a foreign language. Key words: Asynchronous learning; blogging Malay literacy; e-learning; foreign language education; digitised identity.